IAC FRAMEWORK DEVELOPMENT FOR EC2 MIGRATION - Bishnoi, Prevesh Kumar; Dharmender Kumar; Bhanti, Prateek Bhanti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The evolution of a Terraform imported Infrastructure as Code (IaC) framework for EC2 migration investigated in this research. It guarantees consistency, automates deployment, and boosts scalability, hence lowering hand-made errors. Comparative study of the framework with conventional, non-IaC methods shows effectiveness increases. It is found that there are various advantages are error free, faster provisioning, than manual migration. Manual provisioning without IaC generates higher risk, more running costs, and discrepancies. The analogy underlines IaC’s changing capacity in cloud computing management. AWS, Azure and GCP and local Virtual box are selected for migration and inter cloud migration.